2022
DOI: 10.30574/gscbps.2022.21.1.0385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taraxacum officinale L. ethanol extract against kidney injuries induced by paracetamol in rats

Abstract: Background/Aim: The biochemical effects of dandelion (D) ethanol extract on blood and renal tissue in rats induced by paracetamol (PRC) were examined in this study. Methods: In this study was utilized 36 Sprague Dawley male rats, aged 5 months. Rats were divided 6 groups of 6 rats each, randomly. Control group (C), D200 group, D250 group, PRC group, PRC+D200 group, PRC+D250 group, was given orally per os (p.o) in a single dosage (2 g/kg/b.w.) and dandelion extract (200-250 mg/kg) was given intraperitoneally (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Dandelion contains many antioxidants, and antiinflammatory and antimicrobial agents including terpenes, phenolic acids, flavonoids, alkaloids, peptides, oligosaccharides, polysaccharides, calcium, potassium, vitamins A, C, and nicotinic acid, with therapeutic effects on obesity, cancer, heart disease, diabetes, and gastrointestinal disorders (8,10,49) .…”
Section: Dandelion (Taraxacum Officinale)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dandelion contains many antioxidants, and antiinflammatory and antimicrobial agents including terpenes, phenolic acids, flavonoids, alkaloids, peptides, oligosaccharides, polysaccharides, calcium, potassium, vitamins A, C, and nicotinic acid, with therapeutic effects on obesity, cancer, heart disease, diabetes, and gastrointestinal disorders (8,10,49) .…”
Section: Dandelion (Taraxacum Officinale)mentioning
confidence: 99%
“…Studies have shown that dandelion extract can reduce the severity of paracetamol-induced liver damage by boosting antioxidant activity, inhibiting lipid peroxidation, activating the Nrf-2/HO-1 pathway, and inhibiting the apoptosis pathway (8,10,49,50) . The animal dosage used in these studies ranges from 100-400 mg/kg/day.…”
Section: Dandelion (Taraxacum Officinale)mentioning
confidence: 99%